2020
DOI: 10.1167/tvst.9.10.25
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Foveal Avascular Zone in Deep Capillary Plexus Is Associated with Better Visual Acuity in Patients after Macula-off Retinal Detachment Surgery

Abstract: Smaller foveal avascular zone in deep capillary plexus is associated with better visual acuity in patients after macula-off retinal detachment surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Ng et al associated the change in the FAZ and VD with final BCVA in eyes after macula-off RRD surgery, and investigated the evolution of FAZ and VD during 12 months of follow-up. At 12 months postoperatively, FAZ difference of the DCP and BCVA difference were correlated, and there was no evidence that FAZ and VD changed during followup [19].…”
Section: Plos Onementioning
confidence: 87%
“…Ng et al associated the change in the FAZ and VD with final BCVA in eyes after macula-off RRD surgery, and investigated the evolution of FAZ and VD during 12 months of follow-up. At 12 months postoperatively, FAZ difference of the DCP and BCVA difference were correlated, and there was no evidence that FAZ and VD changed during followup [19].…”
Section: Plos Onementioning
confidence: 87%
“…Retinal microvasculature of the two capillary plexuses (SCP and DCP) and choriocapillary network are evaluated in detail, while ICP is not always included in most studies due to projection artifact [9][10][11]. Notably, the currently available evidence concerning potential macular alterations as seen on OCT-A after RRD repair has stirred controversy as the results of the studies have not been unequivocally confirmed [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…Obviously, gas is a widely utilized tamponading agent and its use accounts for a large fraction of cases [32][33][34][35][36][37][38][39]. Indeed, most studies comprehensively examine OCT-A characteristics of RRD eyes after PPV with gas tamponade [13][14][15][16][17][18][19][20][21][22][23][29][30][31], while there is limited evidence of those treated by PPV with SO or by scleral buckle [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The primary anatomical success rates for RRD repair by PPV have been found to range from 64% to 96%.…”
mentioning
confidence: 99%
See 2 more Smart Citations